2020
DOI: 10.3390/antiox9050359
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Antioxidant Effects of Ascorbic Acid and Alpha Lipoic Acid (in Liposomal Forms) as Adjuvant in Cancer Treatment

Abstract: Antioxidants are known to minimize oxidative stress by interacting with free radicals produced as a result of cell aerobic reactions. Oxidative stress has long been linked to many diseases, especially tumours. Therefore, antioxidants play a crucial role in the prevention or management of free radical-related diseases. However, most of these antioxidants have anticancer effects only if taken in large doses. Others show inadequate bioavailability due to their instability in the blood or having a hydrophilic natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 97 publications
0
35
0
Order By: Relevance
“…ALA reduces chemotherapy side effects having a substantial role in potentiating and synergizing the cytotoxic effect of antineoplastic agents while protecting normal body tissue, increasing patient survivability [53]. ALA's anti-proliferative effect on tumor cells is due to the increased reduction in epidermal growth factor receptor expression ErbB2 and ErbB3 [54].…”
Section: Ala and Cancermentioning
confidence: 99%
“…ALA reduces chemotherapy side effects having a substantial role in potentiating and synergizing the cytotoxic effect of antineoplastic agents while protecting normal body tissue, increasing patient survivability [53]. ALA's anti-proliferative effect on tumor cells is due to the increased reduction in epidermal growth factor receptor expression ErbB2 and ErbB3 [54].…”
Section: Ala and Cancermentioning
confidence: 99%
“…ALA works on the cellular level to help produce energy in the body, as a part as, a coenzyme in the citric acid cycle by preparing the fuel for the mitochondria, and plays a vital role in mitochondrial electron transport reactions required for cellular energy production (15). It has been reported that ALA have powerful antioxidant abilities, equal to that of coenzyme Q 10, vitamin C, and vitamin E (16). Unlike other antioxidants, ALA alpha lipoic acid has ability to neutralize free radicals in intracellular and extracellular environments (17).…”
Section: Introductionmentioning
confidence: 99%
“…The excess of reactive oxygen species (ROS) can damage cellular lipids, proteins or DNA. Oxidative imbalance has been implicated in a number of diseases, including cancers, atherosclerosis and heart diseases, as well as the ageing process [ 18 ]. The DPPH and ABTS free radical scavenging assays have been widely accepted for estimating the free radical scavenging activities of antioxidants.…”
Section: Discussionmentioning
confidence: 99%